2018
DOI: 10.1037/gdn0000085
|View full text |Cite
|
Sign up to set email alerts
|

Determining the components of cohesion using the repertory grid technique.

Abstract: Cohesion enhances positive workplace outcomes, including job satisfaction, team performance, and productivity. Despite the importance of cohesion, definitions, factors, and measures of cohesion are used inconsistently. For example, the contribution of both task and social cohesion has been highlighted in previous research but ignored by other researchers in cohesion. This exploratory study examined the components of cohesion using a repertory grid technique and weighted multidimensional scaling. Twenty-six par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Mullen and Copper (1994), for example, examined the elements identified in some of the earliest conceptions of cohesion: Interpersonal attraction, task commitment, and pride in one’s group. Von Treuer et al (2018), using inductive procedures, concluded cohesion includes at least six distinguishable components: Commitment to goals, identify and respect, interpersonal warmth, a sense of belonging, pride in the group’s achievements, and a shared positive group-level identity. Carron and his colleagues, in their work with sports teams, considered cohesion to be based on social attraction, engagement in the group’s tasks, and members’ beliefs about the group’s social and task unity (e.g., Carron & Brawley, 2000).…”
Section: A Unitary Theory Of Group Cohesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mullen and Copper (1994), for example, examined the elements identified in some of the earliest conceptions of cohesion: Interpersonal attraction, task commitment, and pride in one’s group. Von Treuer et al (2018), using inductive procedures, concluded cohesion includes at least six distinguishable components: Commitment to goals, identify and respect, interpersonal warmth, a sense of belonging, pride in the group’s achievements, and a shared positive group-level identity. Carron and his colleagues, in their work with sports teams, considered cohesion to be based on social attraction, engagement in the group’s tasks, and members’ beliefs about the group’s social and task unity (e.g., Carron & Brawley, 2000).…”
Section: A Unitary Theory Of Group Cohesionmentioning
confidence: 99%
“…Burlingame et al (2018) judge cohesion to be “the most popular of the relationship constructs in the group therapy literature” (p. 384) but they also note that “the construct validity and criterion validity of cohesion measures are weak” (p. 393). Dion (2000, p. 21) laments “At present we have little or no idea as to how different putative measures of cohesion in our current toolbox relate to one another.” Von Treuer et al (2018) conclude “cohesion is a complex construct and current frameworks of cohesion may be too simplistic for capturing its true complexity.” These empirical and theoretical uncertainties pertaining to cohesion can be traced to a number of sources, including a marked diversity in the number of ways theorists and researchers have defined and assessed the concept.…”
Section: A Unitary Theory Of Group Cohesionmentioning
confidence: 99%
“…Support for the task/social distinction appears strong even in nonphysical activity settings (Casey-Campbell & Martens, 2009). However, examination of cohesion in a youth sports (Eys, Loughead, Bray, & Carron, 2009) and the work setting (von Treuer, McLeod, Fuller-Tyszkiewicz, & Scott, 2018) provided no support for the individual versus group component of cohesion. This failure to find backing for the individual/group distinction could be an aberration given that a measure developed for the university classroom using the conceptual framework supported the original two-dimension model (Bosselut, Heuze, Castro, Fouquereau, & Chevalier, 2018).…”
Section: Cohesionmentioning
confidence: 95%
“…Social cohesion involves group members developing positive interpersonal relationships with one another(von Treuer et al, 2018). Although virtual participants did not express feelings of group social cohesion as important, both participant groups viewed relationship building as an essential aspect of individual social cohesion.…”
mentioning
confidence: 87%
“…An example might be group member's wish to cultivate positive relationships with other group members (von Treuer, McLeod, Fuller-Tyszkiewicz, & Scott, 2018).…”
Section: Task and Social Cohesionmentioning
confidence: 99%